Nonradiative and Radiative Recombination in CdS Polycrystalline Structures - E. Gaubas; V. Borschak; I. Brytavskyi; T. Čeponis; D. Dobrovolskas; S. Juršėnas; J. Kusakovskij; V. Smyntyna; G. Tamulaitis; A. Tekorius (Advances in Condensed Matter Physics)
Properties of polycrystalline CdS layers, employed in formation of the CdS-Cu2S heterostructures, have been studied by combining contactless techniques of the time and spectrally resolved photoluminescence (TR-PL) spectroscopy and microwave-probed photoconductivity (MW-PC) transients. The confocal microscopy has been employed to correlate the homogeneity of photoluminescence and grain size in CdS layers. Three types of samples with crystallite grain size of <1 μm (the I-type) and of 2–10 μm of homogeneous (II-type) and inhomogeneous (III-type) grain distribution have been separated. The simultaneous record of MW-PC and TR-PL responses ensures the same sampling area on the layer under investigation, as both (MW-PC and TR-PL) signals are generated by the same UV laser excitation beam. Two PL bands peaked at 500 and 700 nm were revealed. It has been demonstrated that photoluminescence intensity strongly depends on the properties of the polycrystalline 15–26 μm thick CdS layers with equilibrium carrier density of about 1.5×1013 cm−3, which serve as the substrates to form CdS-Cu2S junctions. The different carrier decay components were ascribed to different microareas with characteristic MW-PC and PL decay lifetimes of 2–10 ns, ascribed to microcrystallites with PL instantaneous decay lifetimes of 40–200 ns, and MW-PC decay lifetimes in the range of 100–1000 μs attributed to the inter-crystallite areas of CdS polycrystalline material.